Penerapan Metode Rapid Application Development (RAD) dalam Perancangan Sistem Pemesanan Menu menggunakan Quick Response (QR) Code - Kaban, Roberto; Nasution, Ricky Julian (MEANS (Media Informasi Analisa dan Sistem), 2020)
Cafe business that provides food and beverage menus is a fast growing business today. 99's Coffee located in Tanjung Pura is a cafe that wants to further optimize service to consumers by simplifying the process of ordering food and drinks. The purpose of this research is to design an ordering system to make it easier for customers to order menus and business owners to manage orders. The method used in designing this system is Rapid Application Development (RAD). The stages in the RAD consist of Requirements planning, Design Workshop and Implementation. The system was built using the PHP programming language with the Codeigniter Framework, the system display uses the Bootstrap CSS Framework and data storage uses MariaDB. The result of this research is a system that allows customers to order food and beverage menus by simply scanning the Quick Response (QR) Code that has been provided at each customer's table.